Utilization of Opu Daeng Manambon's Biography as a Source of Local History at SMA Negeri 1 Mempawah Hilir - Bimantoro, Farhan Prassetyo; Firmansyah, Haris; Chalimi, Ika Rahmatika (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
This research was conducted to determine the use of Opu Daeng Manambon's biography as a source local history at SMA Negeri 1 Mempawah Hilir . Using this type of research qualitative with descriptive methods. Data sources include interviews with history teachers and curriculum head of SMA Negeri 1 Mempawah Hilir, Mrs. Purmiasih, S.Pd, and Mrs. Agustina, S.Pd, students of XI IPS 2 SMA Negeri 1 Mempawah Hilir, caretaker of the grave of Opu Daeng Manambon Datuk Gusti Amridudin and royal relatives from the Amantubillah Palace, Mrs. Elisa Ruqiyah. Data collection includes observation, interviews, and documentation. The stages of data analysis include data collection, data reduction, data presentation, and verification/conclusion. Data validity techniques use source triangulation and technical triangulation. The research results show that there are three stages in the use of Opu Daeng Manambon's biography, namely: planning, implementation and evaluation stages. Several obstacles were also found , such as limited space for local history in the history syllabus and the impact of the Covid-19 pandemic. Evaluation of learning outcomes is carried out by creating historical comics or poetry.